2012
DOI: 10.1002/jcp.22936
|View full text |Cite
|
Sign up to set email alerts
|

Nandrolone and stanozolol induce leydig cell tumor proliferation through an estrogen‐dependent mechanism involving IGF‐I system

Abstract: Several substances such as anabolic androgenic steroids (AAS), peptide hormones like insulin-like growth factor-I (IGF-I), aromatase inhibitors and estrogen antagonists are offered via the Internet, and are assumed without considering the potential deleterious effects that can be caused by their administration. In this study we aimed to determine if nandrolone and stanozolol, two commonly used AAS, could have an effect on Leydig cell tumor proliferation and if their effects could be potentiated by the concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…The combination of nandrolone and stanozolol with IGF-I increased E2 production to levels higher than those obtained with the use of each single agent. We have recently shown that the two AAS increase IGF-I production in a tumor Leydig cell line (Chimento et al, 2012) and potentially a similar effect could also occur in MCF-7 cells. Thus, when IGF-I was used in combination with nandrolone and stanozolol, the amount of IGF-I available to the cells was higher than the concentration used to originally treat the cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The combination of nandrolone and stanozolol with IGF-I increased E2 production to levels higher than those obtained with the use of each single agent. We have recently shown that the two AAS increase IGF-I production in a tumor Leydig cell line (Chimento et al, 2012) and potentially a similar effect could also occur in MCF-7 cells. Thus, when IGF-I was used in combination with nandrolone and stanozolol, the amount of IGF-I available to the cells was higher than the concentration used to originally treat the cells.…”
Section: Discussionmentioning
confidence: 93%
“…Clinical reports highlight a link between AAS abuse and different kinds of cancer, such as hepatocellular adenomas and adenocarcinomas (Socas et al, 2005). In addition, we have recently reported that AAS, through the activation of estrogen-dependent pathways, are involved in the progression of a type of testicular cancer (Chimento et al, 2012). To date no data regarding the relationship between AAS abuse and breast cancer risk are available.…”
Section: Introductionmentioning
confidence: 97%
“…[23] The attraction of anabolic agents apparently continues to be unconfined among cheating athletes and recreational sportsmen and women despite numerous comprehensive and new reports on health risks attributed to the abuse of AAS, [24,25] ranging from acne fulminans [26] over cardiovascular issues [27][28][29][30][31] to increased risk of breast and Leydig cell cancer [32,33] as well as psychic disorders and dependence. [23] The attraction of anabolic agents apparently continues to be unconfined among cheating athletes and recreational sportsmen and women despite numerous comprehensive and new reports on health risks attributed to the abuse of AAS, [24,25] ranging from acne fulminans [26] over cardiovascular issues [27][28][29][30][31] to increased risk of breast and Leydig cell cancer [32,33] as well as psychic disorders and dependence.…”
Section: Anabolic-androgenic Steroidsmentioning
confidence: 99%
“…This is a matter of concern, since both androgens [44, 45] and HGH [46–49] exhibit cardiac toxicity, raising the specter of synergistic cardiotoxic effects in individuals combining these hormones. Synergistic effects might influence other organ systems as well; one new report suggests that androgens might interact with IGF-1 to enhance Leydig cell proliferation, with a possible increased risk of testicular cancer [25]. …”
Section: Polypharmacymentioning
confidence: 99%
“…These studies include, for example, investigations of androgen effects in animal models, including several new studies of mechanisms for androgen-induced aggression [1720] and possible androgen-related depression [21]. Recent animal studies have also pursued mechanisms of the performance-enhancing effects of androgens (for review see [22]), as well as androgen-induced adverse effects, including cardiac [23], neuronal [24], and possible carcinogenic effects [25]. We will not attempt a complete review of these animal studies here, since this review is focused primarily on illicit human androgen use, but important animal studies of immediate relevance to human androgen abuse are mentioned in the text that follows.…”
Section: Introductionmentioning
confidence: 99%